Latihan ROM Pasif Unilateral dan Bilateral terhadap Peningkatan Kekuatan Otot Akibat Stroke Iskemik - Ratna Fithriyah Sholihany; Agung Waluyo; Diana Irawati (Jurnal Keperawatan Silampari, 2021)
This study aims to compare the effectiveness of unilateral ROM and bilateral ROM exercises to increase muscle strength in post-hospitalized clients with hemiparesis due to ischemic stroke. The research method used is a quasi experimental two group pre and post test design. The results showed that there was an effect of both groups on increasing muscle strength with a p-value of 0.000, in conclusion, bilateral ROM exercises had a higher impact on increasing muscle strength compared to unilateral ROM exercises. Keywords: Muscle Strength, Bilateral ROM, Unilateral ROM, Ischemic Stroke